Arecoline regulates glycolipid and endoplasmic reticulum metabolisms in adult grass carp (Ctenopharyngodon idella) - Liangqin Wu; Na Yao; Weidan Jiang; Pei Wu; Yang Liu; Yaobin Ma; Hongmei Ren; Xiaowan Jin; Hequn Shi; Xiaoqiu Zhou; Lin Feng (Animal Nutrition)
Arecoline is an alkaloid extracted from the plant betel nut with important pharmacological effects and is an agonist at muscarinic receptors (M receptors). In this study, we investigated the effects of dietary arecoline supplementation on hepatopancreatic and muscle glycolipid metabolism in adult grass carp (Ctenopharyngodon idellus). A total of 450 healthy adult grass carp with an initial body weight of 607.87 ± 1.82 g were randomly divided into six experimental groups and fed six levels (0, 0.5, 1.0, 1.5, 2.0, and 2.5 mg/kg diet) of arecoline for 60 days. The results showed that feed supplemented with 1.0 mg/kg arecoline up-regulated mRNA levels of M3, and promoted glucose (GLU) and fatty acid metabolism (P < 0.05) both in hepatopancreas and muscle. The promotion of glycolipid metabolism by arecoline can be achieved through three pathways. Firstly, arecoline alleviated endoplasmic reticulum (ER) stress in grass carp muscle by suppressing the mRNA levels of ER stress-related genes atf4, chop, ire1, and xbp1 as well as the protein expression of p-PERK and p-IRE1 (P < 0.05). Secondly, arecoline protected mitochondrial function by promoting the mitochondrial respiratory chain complex I–V-related protein expression and triggering the mitochondrial unfolded protein response (UPRmt) (P < 0.05). Finally, arecoline promoted close communication between the ER and mitochondria by increasing the expression of the mitochondria-associated endoplasmic reticulum membrane (MAM) tight junction proteins GRP75 and PACS2 as well as the calcium transporter proteins SERCA1 and IP3R, which in turn promoted lipid metabolism by increasing the protein expression of DGAT2 (P < 0.05). In conclusion, we found for the first time that dietary arecoline promoted GLU and fatty acid metabolism in hepatopancreas and muscle, which may be related to the regulatory effects of MAM on ER and mitochondria.